Assessment of the innovation potential of the region when forming a development program - Pishchalkin Denis; Suloeva Svetlana (π-Economy, 2025)
In a modern economy, it is the magnitude of the innovation potential and the efficiency of its use that determine the potential opportunities and growth horizons of the regional economic system. If the innovation potential is at a high level, the region becomes more attractive for investment. Enterprises operating in this area, which are the key elements of the innovation potential, have greater opportunities for innovative development and attracting financing. In turn, the innovative development of the regions is achieved by ensuring competitiveness. Besides isolated development, the region can build stable relationships and achieve effective interaction with other regions in the field of socio-economic development. This allows creating and distributing new products, forming new types of activities, industries and areas of economic activity, thereby enhancing innovative excellence. An assessment of innovation potential is necessary for the development of socio-economic development program, taking into account the efficient use of innovative resources and the justification of innovation policy at different levels of governance. Developing the innovation potential of the region and stimulating innovative activity in society will solve existing problems in the region’s economy and ensure balanced economic growth. The purpose of the study is to develop methodological guidelines for assessing the innovation potential of the region in the formation and implementation of innovative development programs. The article analyzes approaches to the definition of the concept of “innovation potential” and offers an expanded interpretation of this concept by the authors. Then, the analysis and systematization of existing methods for assessing the innovation potential of the region are carried out. At the last stage of the study, methodological provisions have been developed to assess the innovation potential of the region. The scientific significance of the study lies in the development and complementation of theoretical and methodological provisions for assessing the innovation potential of the region, aimed at increasing the objectivity, accuracy, completeness and complexity of the assessment, when developing the program for the innovative development of the region. The practical significance of the study lies in the authors’ conclusions and recommendations, which can be used in assessing the availability of resources (including funding resources) for innovative development program of the region in order to make scientifically sound decisions when forming such a program.